Assessment of the effect of the COVID-19 pandemic on levels of satisfaction in marital relationships during and post-lockdown - Rasha Aziz Attia Salama; Rabab Gad Abd El-Kader; Talaat Matter Tadross; Shaimaa Hashem Elsalous (International Journal of Africa Nursing Sciences)
The current study aimed to assess marital satisfaction during and post the lockdown of the COVID-19 pandemic and explore the factors influencing marital satisfaction among the public. Methods: A cross-sectional study was conducted in Ras Al Khaimah Emirate, United Arab Emirates. A total of 409 respondents participated in a web-based anonymous survey from April to September 2021 and completed sociodemographic and personal characteristics. The Enriching and Nurturing Relationship Issues, Communication and Happiness Marital Satisfaction scale, and the GAD-7 scale were employed in data collection. Bivariate and logistic regression were used to determine the relationship between marital satisfaction and sociodemographic and personal factors. Results: The findings indicated that the mean score of the EMS scale increased significantly after the lockdown in all areas of marital relationships, except for leisure time activities (P = 0.42) and religious orientation (P = 0.47). Marital satisfaction during and after the COVID-19 lockdown was significantly associated with age, gender, education attainment, income, health condition, and anxiety status. Factors such as gender, education, income, and anxiety status have been identified as predictors of marital satisfaction, particularly during the COVID-19 pandemic. Conclusions: The results underscore the importance of considering sociodemographic and personal factors in understanding fluctuations in marital satisfaction during challenging times. They highlight the need to address mental health and emotional well-being within marital contexts, especially during crises. Tailored interventions aimed at enhancing coping strategies, communication skills, and emotional support could help mitigate anxiety’s adverse impact on marital satisfaction, ultimately strengthening relationships and overall well-being.